PERCEPATAN REGENERASI PETANI PADA KOMUNITAS USAHATANI SAYURAN DI KECAMATAN SAMARANG KABUPATEN GARUT PROVINSI JAWA BARAT - aji wahyu santoso; Lukman Effendy; Endang Krisnawati (Jurnal Inovasi Penelitian, 2020)
Abstract Samarang District has the availability of food crops, especially in various vegetable crops to be developed so that it can potentially increase the acceleration of young farmers' regeneration. So, this study aims to describe the characteristics of young farmers, analyze the factors of acceleration of farmers' regeneration, find a strategy of accelerating regeneration. This study was conducted in the Samarang District, Garut Regency. The study sample was 77 respondents who were taken by random sampling technique. The independent variable includes internal factors, namely age, level of education, length of organization, land area, cosmopolitan and external factors of extension activities, government support, availability of facilities and infrastructure, availability of information, and support of informal leaders. The analysis used is descriptive analysis, and multiple linear regression analysis. The results of the study show that managerial is classified as moderate, technically classified as moderate, and socio-economic is classified as moderate Factors related to the acceleration of farmers' regeneration are age, level of education, extension activities, and government support. To increase the acceleration of farmers' regeneration, counseling is carried out by forming the characteristics of farmers and increasing the intensity of extension.